Pengaruh Pengungkapan Sustainability Report terhadap Kinerja Keuangan Perusahaan Finance yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Nisriinaa Faihaa Farhha Azwar; Ratih Kusumastuti; Gandy Wahyu Maulana Zulma (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this study is to determine the impact of sustainability reporting disclosures on financial performance by examining the economic, environmental and social aspects of the company. The companies that became the sample were selected using a purposive sampling method with certain criteria. The sample used in this research is made up of 10 finance sector companies that publish sustainability reports for 2018–2022. Data analysis was carried out, namely descriptive statistical analysis, classical assumption test, panel data regression model, and hypothesis testing using partial test (t test), simultaneous test (f test), and coefficient of determination test (R square) with the help of the Eviews 10 program. The results showed that simultaneously, all dimensions of the sustainability report, namely economic, environmental, and social aspects, have an effect on financial performance (ROE). Meanwhile, partially, the economic aspect of the sustainability report has a significant negative effect on financial performance (ROE), environmental aspects have an effect on financial performance (ROE), and social aspects have no effect on financial performance (ROE).